Voltage Surge Estimation in Inverter-Cable High-Impedance Load System - Wilson, Benjamin Egyin; Armah, Ebenezer; Tsikata, Nutifafa (MSD Institute, 2025)
This paper presents a theoretical analysis of inverter–cable–high-impedance load systems using transmission line theory. High-frequency inverters with short voltage rise times can induce severe voltage surges at the load terminal due to impedance mismatch and wave reflections. An analytical expression is derived to estimate the peak terminal voltage as a function of the inverter rise time and cable propagation delay. Simulation results obtained using MATLAB confirm that the peak voltage can surge up to twice the DC link value (300 V for a 150 V DC source) when the inverter rise time is less than three times the cable propagation delay. To mitigate this overvoltage, a dV/dt filter is designed for worst-case rise-time conditions (step input), enhancing surge suppression without requiring redesign across varying switching speeds. The proposed method offers a practical, cost-effective solution for long-cable applications in high-frequency inverter systems.